The Impact of International Electronic Commerce on Export Trade: Evidence from China - Chenggang Wang; Tiansen Liu; Duo Wen; Dongrong Li; Galash Vladislav; Yu Zhu (Journal of Theoretical and Applied Electronic Commerce Research, 2021)
The impact of international electronic commerce (IEC) on export trade increases along with its expanding scale. Based on relevant data and the gravity model of China’s IEC export trade, this paper develops a theoretical model that can be used in IEC scenarios, applies regression equations, a Hausman test, and other empirical methods to verify relevant data, and performs a robustness test. The purpose of this paper is to explore the mechanism of IEC impact on China’s trade, and hopefully to study the temporal structural changes of the impact of IEC activities on China’s export trade based on the financial crisis and European debt crisis variables. The innovation of this paper is mainly reflected in the large sample of China’s trade selected in this paper. It can also determine the changes in the distance effect of international trade in the era of IEC, and reveal the mechanism by which IEC applications help foreign trade enterprises overcome economic crises. Four key conclusions are obtained as follows. First, the development of IEC has significantly promoted the expansion of China’s export trade scale. Second, in the context of the global financial crisis and European debt crisis, the positive promotion effect of IEC on exports is not significant. Third, the promotion effects of IEC on China’s exports to both developing and industrialized countries are significant, with the impact on developed country exports being slightly greater. Fourth, although the geographical distance for measuring transportation costs has a negative effect on China’s exports, such effect has been greatly weakened.